ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERUBAHAN PERILAKU MEROKOK PADA MAHASISWA UNIVERSITAS SILIWANGI DI MASA PANDEMI COVID- 19 - Aris Muhammad Ramdani; Siti Novianti (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Smoking behavior is a phenomenon that appears in society, where most people already know the negative impact of smoking. The causes of health problems caused by smoking such as lung cancer, heart disease, etc., smoking is also a risk factor for Covid-19 infection. The purpose of this study was to determine the relationship between knowledge, attitude, and frequency of smoking with smoking cessation behavior in Siliwangi University students. The study design used was cross-sectional. The sample used is 291 respondents which are the results of the screening. Sampling technique with Total Sampling. The statistical test administered is Chi-Square with (α=0.05). The results showed that there was a relationship between knowledge (p-value = 0.034 0.05), attitude (p-value = 0.000 0.05) and smoking frequency (p-value = 0.034 0.05) with changes in smoking behavior. Siliwangi University students during the Covid-19 Pandemic. Students need to increase knowledge and information regarding the impact, effects, and dangers of smoking on health, as well as preventing the transmission of Covid-19.